Pérez Zamorano, Abel (2010), Marginación urbana. El caso del oriente mexiquense, México, Universidad Autónoma Chapingo/Centro Mexicano de Estudios Económicos y Sociales/Miguel Ángel Porrúa, 281 p. - Vite Pérez, Miguel Ángel (Estudios Demográficos y Urbanos, 2012)
Pérez Zamorano, Abel. (2010). Marginación urbana. El caso del oriente mexiquense, México, Universidad Autónoma Chapingo/Centro Mexicano de Estudios Económicos y Sociales/Miguel Ángel Porrúa